2001
DOI: 10.1101/lm.36301
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Modifies the PKA-Dependence of Hippocampal LTP and Improves Hippocampus-Dependent Memory

Abstract: cAMP-dependent protein kinase (PKA) is critical for the expression of some forms of long-term potentiation (LTP) in area CA1 of the mouse hippocampus and for hippocampus-dependent memory. Exposure to spatially enriched environments can modify LTP and improve behavioral memory in rodents, but the molecular bases for the enhanced memory performance seen in enriched animals are undefined. We tested the hypothesis that exposure to a spatially enriched environment may alter the PKA dependence of hippocampal LTP. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
211
4
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(250 citation statements)
references
References 66 publications
26
211
4
4
Order By: Relevance
“…In all age groups, enrichment attenuated contextual freezing. Even if this result is inconsistent with previous studies showing that enrichment tended to increase contextual fear (Briand et al 2005;Duffy et al 2001;Tang et al 2001), we previously showed (Barbelivien et al 2006) that if, in adult rats, enrichment increased fear to a background context (i.e., when a tone perfectly predicts footshock occurrence), it concomitantly decreased fear to a foreground context (i.e., no predictive tone), as found in the current study at all ages. Therefore, the lower freezing scores that we observed in enriched rats may reflect a genuine decrease in fear rather than a deficit in contextual conditioning.…”
Section: Emotional Behaviorscontrasting
confidence: 99%
See 1 more Smart Citation
“…In all age groups, enrichment attenuated contextual freezing. Even if this result is inconsistent with previous studies showing that enrichment tended to increase contextual fear (Briand et al 2005;Duffy et al 2001;Tang et al 2001), we previously showed (Barbelivien et al 2006) that if, in adult rats, enrichment increased fear to a background context (i.e., when a tone perfectly predicts footshock occurrence), it concomitantly decreased fear to a foreground context (i.e., no predictive tone), as found in the current study at all ages. Therefore, the lower freezing scores that we observed in enriched rats may reflect a genuine decrease in fear rather than a deficit in contextual conditioning.…”
Section: Emotional Behaviorscontrasting
confidence: 99%
“…The enrichment-induced neurobiological modifications that might explain effects on memory persistence are numerous. Indeed, environmental enrichment increases hippocampal neurogenesis and survival of newly formed neurons (e.g., Bruel-Jungerman et al 2005), CREB activation (e.g., Williams et al 2001), long-term potentiation (Duffy et al 2001), and brain-derived neurotrophic factor levels (Bakos et al 2009). All these factors contribute to consolidation and thus memory persistence (Bekinschtein et al 2007;Bruel-Jungerman et al 2005;Sekeres et al 2010;Suzuki et al 2011).…”
Section: Spatial Learning and Memorymentioning
confidence: 99%
“…However, it seems more likely the elevation is physiological since the elevation of corticosterone is diurnal-with an even greater elevation compared to non-enriched animals in the p.m. (de Jong et al, 2000;. Such phasically elevated corticosterone is known to improve learning and memory (De Kloet et al, 1999;Diamond et al, 1992), a principal neurological consequence of environmental enrichment (Duffy et al, 2001). …”
Section: Exemplary Cytokine and Changesmentioning
confidence: 99%
“…The most welldocumented augmentation of learning after complex housing is in spatial tasks such as the Morris water maze and Hebb-Williams maze (Pham et al 1999;Kobayashi et al 2002). However, there is also evidence that environmental enrichment enhances Pavlovian fear conditioning in mice (Rampon et al 2000;Duffy et al 2001;Tang et al 2001).Although these examples of experience-dependent plasticity are clearly advantageous, this is not true of all forms of experience-dependent plasticity. Repeated treatment with psychostimulant drugs, for example, also leads to an increase in dendritic branching and spine density in a number of brain regions, which is thought to be related to the development of behavioral sensitization (Robinson and Kolb 1997, 1999Robinson et al 2001; Li et al 2004).…”
mentioning
confidence: 98%